(3QSGdI aj GdeMGHGI hGdHjY GdeTQhWs - (3GdHgHgGfj, eMeO GdHgHgGfj, eMeO HGbQ Hf eMeO Cced GdCUagGfj, J (B1205(3g` (B1891(3es ((3cQHdGAs)
(3ChdgG (B:s
(3ChdgG(B: (3GdMeO ddg QH GdYGdejf (B... (3Ef LekYG ef YdeGA gPG GdReGf CjOge Gddg GYJbOhG MdjI GdbQV HTQW GdeYGedI GdeMGHGJjI heQGOj efgG Cf jHjY GdebQV ef GdeSJbQV HCRjO ef CLQgs
(3BNQgG (B:s
(3BNQgG(B: (3aJOHQ Ke Ef GdWeY hGdfjI gh eKd eG jgOj GdabjQ Edi GdCZfjGA WekYG efge aj GdYhV HCRjO Hd hCVYGag heKd eG jQTj Edi GdMcGe hGdbVGI ddMce dge heKd Cf JDNP HfJ QLd HYfhGf GdfcGM WekYG aj GdHcGQI Ch GdhLGgI ef Ohf TQWs
(3GdJhKjbGJ GdeQLYjI (B:s
(3eYLe GdeDdajf L (B3: 154s
(3GdPQjYI, L (B17: 49s
(3eUOQ GbJfGA GdCUd (B:s
(3cGTa GdZWGAs
(3ehGUaGJ GdhYGA (B:s
Keywords: (3abg GdePGgH GdCNQis